PENGARUH LAYANAN PENGUASAAN KONTEN DENGAN LATIHAN BERPIDATO TERHADAP PENINGKATAN KEPERCAYAAN DIRI SISWA KELAS X SMA N 14 PEKANBARU T. A 2015/2016 - Mona Desrianty; Zulfan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aimed to describe the self-confidence of students before given exercises speech, to find out how the process of service delivery, to find a picture after a given practice speech, differences in the confidence of students before with after practice speech and to see the difference in the confidence of students in the experimental group with the control group as well as the influence of mastery of content services with speech exercises. These research subjects Class X High School n 14 Pekanbaru totaling 60 students. The results of this study are given practice a speech before the confidence of the students were low category (50%). Service delivery process is done four times. After the implementation of speech exercises self-confidence of students at the high category (57%), this proves that there are significant differences between the self-confidence of students before and after the speech exercises. Then to see the differences in the experimental group and control group then used the formula Independent sample t test in SPSS with the t = 5.846 with sig (2-tailed) of 0.000. Because the value sig (2-tailed) 0.000 <0.005, it can be concluded "there is a difference between the students' confidence in the experimental group and control group. As for the contribution of services to the exercise mastery of content addressed to the increased confidence of students that is equal to 57%.Key Words : Service Content overs, speech training, self-confidence of students